A Pilot Study of the Relationship Between Pregnancy and Autoimmune Disease: Exploring the Mother’s Psychological Process - Cataudella, Stefania; Lampis, Jessica; Agus, Mirian; Casula, Fabiana; Monni, Giovanni (Frontiers in Psychology, 2019)
Autoimmune disease mainly affects women in their reproductive years and has a significant impact on childbearing. Pregnancy can induce an improvement of the mother’s symptomatology in some diseases such as rheumatoid arthritis while exacerbating or having no effect on other autoimmune diseases as multiple sclerosis (Borchers et al., 2010). This uncertainty can affect the process of psychological reorganization, which leads to the acquisition of a maternal identity. The quality of the mother-fetus emotional bond is considered particularly relevant for the subsequent attachment relationship and the psychological development of the infant (Ammaniti et al., 2013). In the last trimester of pregnancy, 15 women with different autoimmune diseases were interviewed using the IRMAG-R (Ammaniti and Tambelli, 2010). They also completed a battery comprising: PAI (Della Vedova et al., 2008); MAAS (Busonera et al., 2016); DAS (Gentili et al., 2002); PBI (Scinto et al., 1999); MSPSS (Prezza and Principato, 2002); Difficulties Emotional Regulation Scale (DERS, Giromini et al., 2012); CES-D (Fava, 1983); HCR-TS (Bova et al., 2012). All interviews were audiotaped, transcribed verbatim, and analyzed by Atlas.ti. The results show that women with autoimmune disease were ambivalent toward pregnancy, had high levels of depression, had difficulties in recognizing physical and psychological changes, and had difficulties in imagining the child. These are considered risk factors that could negatively affect the postnatal caregiving system. These results focus on the importance of early multidisciplinary interventions that can support expectant women when they show signs of relationship difficulties with their infants prior to his/her birth.